The Impact of Reference Interest Rates, Bond Investments and Exchange Rates on Financial Market Dynamics - Daariin Dewi Nabiilah; Nur Imroatus Sholikah; Nanda Lutfiah Cahya May Salva; Adinda Nibros Zahira Fasya; Maria Yovita R Pandin (Lead Journal of Economy and Administration, 2025)
The main focus of this study is to analyze how the benchmark interest rate, bond investment, and exchange rate affect the dynamics of the financial market in Indonesia in 2024. The method applied is quantitative by using secondary data from Bank Indonesia, and data processing is carried out using SPSS software. The sample used is secondary time series data, which is generally quantitative and obtained from official sources such as Bank Indonesia. This kind of data is very relevant and credible to measure the relationship between macroeconomic variables such as interest rates, exchange rates, and bond investment on financial market dynamics. This study uses independent variables including benchmark interest rates, bond investment, and exchange rates. And the dynamics of the financial market are the dependent variables.